A Review of Microstructural Alterations around Nonmetallic Inclusions in Bearing Steel during Rolling Contact Fatigue. Issue 6 (1st November 2016) - Moghaddam, Sina Mobasher; Sadeghi, Farshid
ABSTRACT: Microstructural alterations in bearing steels during rolling contact cycling have been reported in the literature for more than 60 years. These changes appear in different shapes and locations. One class of such alterations is "butterfly wings": regions of microstructurally transitioned material that appear diagonally around nonmetallic inclusions and may serve as fatigue crack initiation sites. Over the course of the past half a century numerous experimental and multiple analytical efforts have been made to understand and model this phenomenon, yet a lot is to be discovered and understood about root causes and mechanisms leading to butterfly formation. This article presents a comprehensive overview of the crack nucleation phenomena due to butterfly formation, its characteristics, and its negative impact on bearing service life. Significant attempts that have been made to solve the problem over the past half a century are mentioned, with a focus on recent work. Unanswered dilemmas are particularly discussed to highlight avenues of future research.